Evaluation of Using Odua Weston Jambi Hotel Services: The Influence of Internship Student Service Quality on Consumer Satisfaction - Ariani, Eka; Patrick, Bungo; Karimi, Mina (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The aim of this research is to analyze the influence of student interns on service quality and consumer satisfaction in using the services of the O2 Weston Hotel in Jambi, which is an important factor in improving the guests' stay experience. Methodology: This research method uses a quantitative approach by randomly sampling 60 consumers of the Odua Weston Hotel in Jambi. Data was collected through a survey using a questionnaire compiled based on variables related to service quality and consumer satisfaction. Data analysis was carried out using a regression test to measure the relationship between the variables involved in this research. Main Findings: The research results show that there is a significant relationship between service quality and consumer satisfaction in using the services of the Odua Weston Hotel in Jambi. Regression analysis shows that service quality has a strong positive influence on consumer satisfaction, with a high and statistically significant regression coefficient value. This shows that the higher the quality of service provided by the hotel, the higher the level of consumer satisfaction. Novelty/Originality of this study: The novelty of this research lies in the approach of using regression methods to explore in depth the influence between service quality and consumer satisfaction at the Odua Weston Hotel in Jambi, which provides a valuable contribution in strengthening understanding of the factors that influence consumer satisfaction in the context of the hotel industry.